Comparative analysis of the digestive system’s anatomical parts in two zoophagous bird species: White Stork (Ciconia ciconia) and Common Buzzard (Buteo buteo) - Alexandra-Iulia PREJA; Călin Csaba POP; Irina MOLDOVAN; Alexandru N. STERMIN; Aurel DAMIAN (Studia Universitatis Babeș-Bolyai. Biologia)
Aristotle in his anatomical observations is marking the beginning of functional anatomy followed by Georges Cuvier that formulate the low of the correlation of parts. According with this we can expect that the digestive system structures tend to be similar between species that consume approximately the same type of food. In this study we chose to evaluate macroscopic the digestive system of two different zoophytophagous species, with similar body size but different life behavior and feeding strategies: White Stork (Ciconia ciconia) and Common Buzzard (Buteo buteo). Data were collected after the dissection of 10 carcass (5 White Stork and 5 Common Buzzard). The digestive tract and its structures were measured and weighed. In common buzzard the beak is strong and short adapted for the laceration of the prey. In white stork the beak is long, strong, straight adapted to capture prey like a harpoon. In both species, the esophagus is located on the right side of the neck, the length is different, proportional to the neck. In common buzzard the crop is present and absent in white storks. The cuticle or koilin layer is highlighted in white stork compared to common buzzard. In common buzzard, the small intestine is reduced in size, without marked transition between the duodenum and the ileum. The white storks have a long small intestine with many loops, with no transition between the segments. In both species, the cecum is reduced in size and has a vestigial appearance; the colon is reduced in size, and extends from the level of the ileo-colic junction to the cloaca. The digestive system is adapted to a strictly carnivorous diet and the differences identified between the anatomical structures of the digestive tract of the two species are correlated with the differences of their feeding behavior.